1968
DOI: 10.1021/ac60260a009
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and spectrophotometric study of isomeric stilbenediol intermediates in the reduction of benzil in acid solution

Abstract: The electrochemical reduction of benzil in aqueous-alcohol media has been the subject of several investigations. Polarographic studies indicate that the reduction is irreversible and requires two electrons over the pH range 2 to 10. It has been suggested that the reduction initially produces stilbenediol, which slowly rearranges to give benzoin, the latter being detected only at sufficiently long times after the electrolysis (1).More recently, reduction of benzil electrochemically at the mercury electrode and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The reduction processes observed between −1.2 V and −1.6 V are possibly due to interactions of the anion radical with the EMIm cation, similar to behavior seen by Evans after addition of alkaline earth salts to acetonitrile/benzil solutions 14 and as reported for 9-fluorenone in this system. 29 As was the case for benzil in acetonitrile above, the scan rate dependence of the benzil voltammetry in EMIm BF 4 suggests the involvement of a slow step in the reduction pathway, the most likely nature of which is a proton abstraction from the EMIm cation. 28,29 The reaction scheme given in Figure 3 is consistent with the voltammetry shown in Figure 2.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The reduction processes observed between −1.2 V and −1.6 V are possibly due to interactions of the anion radical with the EMIm cation, similar to behavior seen by Evans after addition of alkaline earth salts to acetonitrile/benzil solutions 14 and as reported for 9-fluorenone in this system. 29 As was the case for benzil in acetonitrile above, the scan rate dependence of the benzil voltammetry in EMIm BF 4 suggests the involvement of a slow step in the reduction pathway, the most likely nature of which is a proton abstraction from the EMIm cation. 28,29 The reaction scheme given in Figure 3 is consistent with the voltammetry shown in Figure 2.…”
Section: Resultsmentioning
confidence: 86%
“…30 EMIm Cl was prepared 31 by reaction of chloroethane and 1-methylimidazole (Aldrich), and EMIm BF 4 was prepared by metathesis of EMIm Cl and NaBF 4 (Aldrich) in acetone, using purification method B. 32 1-Butyl-2,3-dimethylimidazolium tetrafluoroborate (BDMIm BF 4 ) was prepared by metathesis of BDMIm Cl and NaBF 4 . 33 All ionic liquids were dried on a high-vacuum line at 70…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is a nonhomogeneous formation of the photolytically generated intermediate, and The literature values of the pK^ and k are 9.2 and 1.1 X 10® sec'i respectively (15 (36,60,128,133), water (87,90), and hydrocarbons (7,35,43) as solvents. (138,139). These workers concluded that in acidic and neutral solutions, benzll is electrochemically reduced by an irreversible, twoelectron process to stilbendiol which has two geometric forms.…”
mentioning
confidence: 99%
“…These workers concluded that in acidic and neutral solutions, benzll is electrochemically reduced by an irreversible, twoelectron process to stilbendiol which has two geometric forms. Two anodic peaks were obtained using cyclic voltammetry at a stationary mercury electrode, and they were concluded to result from the oxidation of the els-and transstilbendiol; the anodic peak for the cis-lsomer was about 90 mV more positive than the peak for the trans-isomer (39,138). Stilbendiol undergoes a rearrangement, called ketolizatlon, to benzoin.…”
mentioning
confidence: 99%
See 1 more Smart Citation